A significância do conjunto arquitetônico e paisagístico da Praça Torquato de Almeida - Pará de Minas/MG - Cleysi-mara Pinto de Souza (2017)
This work aims at finding out the meanings and the values of the architectural complex (historical center) Torquato de Almeida square in Pará de Minas, state of Minas Gerais, and in an attempt to understand its significance and value at present. The several changes and the disfigurement of this architectural complex which has taken to choose the study object of this work. Thus, it aims at arising questions which allows us understand the recognition of Torquato de Almeida square complex as an asset for the society, showing the physical significant changes occurred on the square since its formation. In order to reach to this aim, the document analysis, heritage dossier of the squares, interview with two distinct groups of people, direct observation in loco and theoretical analysis according to references about the subject were used as methodology. From this methodology it will be possible get information about the study as well as interpret the values finding out the significance of the architectural complex (historic center) Torquato de Almeida square for society. Within the results it is also expected reach the basis to support the other fields of historical interest which pass by a process similar to this and, thus, contribute to solve problems based on this case study.